THE USE OF ANTCONC IN PROVIDING LEXICAL AND SINTACTICAL INFORMATION OF THE TEXBOOK OF RADIOGRAPHIC POSITIONING AND RELATED ANATOMY: A CORPUS LINGUISTIC STUDY - Euis Reliyanti Arum; Wiwin Winarti (Jurnal Sosioteknologi, 2019)
English is considered to be difficult due its different natures with Bahasa Indonesia both in pronouncing and writing. However, English textbooks are widely used in many program studies including in radiology. Therefore, many students have difficulties in understanding and comprehending the books due to their limited English ability especially related to English vocabularies and grammatical. This study aimed to acknowledge lexically and syntactically the linguistics features used in the textbook of Radiographic Positioning and Related Anatomy, which is a must-read book used during the study in the study program of Radiology. The method applied in this Corpus Linguistic study was a combination of quantitative method by using a concordancer called AntConc to analyze the radiology book quntitatively to get the word frequency list, and qualitative method in analyzing the quantitative data to describe the language features used in the textbook. The results of the quantitative and qualitative analyses show the most common vocabularies, word classes, and sentence patterns used in the text book that will be used to compose a pocket dictionary, which will help the radiography students to understand the radiological terms and comprehend many radiological sources autonomously and easily. Furthermore, through the dictionary, the students will not only be able to understand and comprehend many radiological texts but they will also be able to write texts and even discuss radiological topics in English autonomously. Results of the study show that AntConc has benefited the researchers since it has been able to assist the researchers in providing needed lexical and syntactical information of the textbook.  Bahasa Inggris dianggap sulit karena berbeda dengan bahasa Indonesia baik dalam pengucapan maupun penulisannya. Walaupun demikian, di Indonesia buku-buku teks berbahasa Inggris banyak digunakan di berbagai program studi termasuk di bidang radiologi. Oleh karena itu, banyak mahasiswa mendapatkan kesulitan untuk mengerti dan memahami buku-buku berbahasa Inggris tersebut karena keterbatasan pengetahuan Bahasa Inggris mereka terutama berkaitan dengan kosakata dan gramatika bahasa Inggris. Penelitian ini bertujuan untuk mengetahui fitur linguistik dalam bentuk kosakata dan gramatika yang digunakan dalam buku Radiographic Positioning and Related Anatomy. Buku ini merupakan buku yang wajib dipelajari mahasiswa di Program Studi Radiologi. Penelitian ini menggunakan metode gabungan antara kuantitatif dan kualitatif. Dengan menggunakan perangkat lunak konkordansi AntConc data dianalisis secara kuantitaif untuk mendapatkan daftar kata berdasarkan kekerapannya. Selanjutnya, metode kualitatif diaplikasikan untuk menganalisis dan menjelaskan data yang dihasilkan. Analisis kuantitatif dan kualitatif tersebut menghasilkan daftar kosakata, kelas kata, dan pola kalimat yang sering muncul dan akan digunakan untuk menyusun kamus mini buku tersebut. Keberadaan kamus ini diharapkan dapat membantu mahasiswa radiologi untuk memahami terminologi radiologi dan memahami banyak teks radiologi secara mandiri dengan mudah. Lebih lanjut lagi, mahasiswa tidak hanya mampu memahami banyak teks radiologi tetapi juga mampu memproduksi teks, bahkan berdiskusi tentang radigrafi dalam bahasa Inggris secara madiri. Hasil penelitian menunjukkan perangkat AntCont telah memberikan manfaat kepada peneliti karena perangkat ini telah mampu membantu peneliti untuk mempersiapkan informasi leksikal dan gramatikal bahasa Inggris yang terdapat pada buku radiologi di atas.